Method for preparing silicon carbide coating on surface of graphite block and composite material

By forming an initial silicon carbide layer on the surface of graphite blocks and performing interface activation treatment, combined with CVD deposition and doping technology, the interface characteristics of the silicon carbide coating are optimized, and the problem of easy peeling of traditional coatings under high temperature conditions is solved, significantly improving the interface bonding strength and high temperature stability.

CN120157515AActive Publication Date: 2025-06-17JIANGXI XINRONG LITHIUM ELECTRIC MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510500988.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2025-06-17
Estimated Expiration
2045-04-21

AI Technical Summary

Technical Problem

Traditional double-layer silicon carbide coatings are prone to peeling or cracking under high temperature cycles or thermal shock conditions, mainly due to insufficient interfacial bonding strength.

Method used

The initial silicon carbide layer is formed by using metal silicon particles to react with graphite blocks under vacuum, and the activity and roughness of the initial layer are improved by using argon plasma etching and hydrogen/nitrogen mixed gas activation treatment. Subsequently, CVD deposition was performed using trichloromethylsilane and methane gas to form a CVD layer, and interface characteristics were optimized by boron trichloride concentration gradient doping and structural gradient CVD deposition.

Benefits of technology

The interface bonding strength and high temperature stability of the silicon carbide coating are significantly improved, the shear strength is increased by 40-60%, and the interface peeling rate is reduced by more than 85%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120157515A_ABST
    Figure CN120157515A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a silicon carbide coating on the surface of a graphite block and a composite material, and solves the technical problems that the interface of the traditional double-layer silicon carbide coating has defects and is easy to peel or crack through a progressive interface optimization system combining interface activation pretreatment and gradient transition layer design. The method comprises the following steps: carrying out silicon steam reaction on metal silicon particles and a graphite block material in a vacuum environment to form an initial silicon carbide layer; performing plasma etching and activating treatment on the initial silicon carbide layer; cVD deposition is carried out by adopting gradient transition layer design of three dimensions of stoichiometric ratio gradient, doping element gradient and structure gradient. The silicon carbide coating prepared by the method shows excellent thermal stability and interface bonding strength under a high-temperature cycle condition, and is particularly suitable for a high-end application scene needing to work in an extreme temperature and thermal shock environment for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of material preparation, and specifically relates to a method for preparing a silicon carbide coating on the surface of a graphite block and a composite material. Background Art

[0002] Silicon carbide-coated graphite composites are widely used in high-end technical fields such as semiconductor manufacturing, aerospace, and nuclear energy due to their combined advantages of high thermal conductivity and low expansion coefficient of graphite, as well as high-temperature oxidation resistance and wear resistance of silicon carbide. Such composites are usually prepared by methods such as chemical vapor deposition (CVD), liquid-phase silicon infiltration, or direct gas-phase silicidation. Among them, the silicon carbide coating prepared by the CVD method has the best purity and denseness.

[0003] Currently, the preparation method of the silicon carbide coating on the graphite matrix mainly includes two key steps: the reaction of silicon vapor to form an initial silicon carbide layer, and the deposition of the outer layer of silicon carbide by the CVD method. During the silicon vapor reaction process, metallic silicon forms silicon vapor at high temperature and directly reacts with carbon atoms on the surface of the graphite matrix to generate an initial silicon carbide layer; subsequently, the outer layer of silicon carbide is deposited on the surface of the initial layer by the CVD method using gas precursors such as trichloromethylsilane to form a silicon carbide coating with a bilayer structure.

[0004] However, there is a significant defect in the traditional method for preparing the bilayer silicon carbide coating: the interfacial bonding strength between the two layers of silicon carbide is insufficient, and it is prone to peeling or cracking under high-temperature cycling or thermal shock conditions. This is mainly due to the inactivity of the surface of the initial silicon carbide layer and the obvious composition and structure mutations between the two layers, resulting in stress concentration at the interface. This defect severely restricts the application of silicon carbide-coated graphite composites under more extreme conditions, and there is an urgent need to develop new interface optimization technologies to solve this problem. Summary of the Invention

[0005] In view of this, this application provides a method for coating the surface of a graphite block with silicon carbide, which solves the problem of defects, peeling, or cracking at the interface of the bilayer silicon carbide coating in the prior art.

[0006] An embodiment of the present application provides a method for preparing a silicon carbide coating on the surface of a graphite block, including: using metal silicon particles and a graphite block to carry out a silicon vapor reaction in a vacuum environment to obtain a graphite block with an initial silicon carbide layer; placing the graphite block with the initial silicon carbide layer in a plasma treatment chamber, performing surface etching via argon plasma, and performing surface activation treatment using a mixed gas of hydrogen and nitrogen to obtain an activated graphite block; using the activated graphite block to carry out CVD deposition according to a preset ratio of trichloromethylsilane and methane gas to obtain a graphite block after CVD deposition; performing CVD deposition with a boron trichloride concentration gradient doping on the graphite block after CVD deposition to obtain a doped graphite block; carrying out structure gradient CVD deposition on the doped graphite block according to a preset temperature and gas flow rate to obtain a silicon carbide coating.

[0007] Preferably, the step of using metal silicon particles and a graphite block to carry out a silicon vapor reaction in a vacuum environment to obtain a graphite block with an initial silicon carbide layer includes: placing metal silicon particles with a particle size of 5-10 mm at the bottom of the reaction device, and placing the graphite block in the reaction device; heating the reaction device to 1700-1800 °C at a heating rate of 10 °C / min under a vacuum degree of 500 Pa and reacting for 2-4 hours to obtain the graphite block with the initial silicon carbide layer.

[0008] Preferably, the step of placing the graphite block with the initial silicon carbide layer in a plasma treatment chamber, performing surface etching via argon plasma, and performing surface activation treatment using a mixed gas of hydrogen and nitrogen to obtain an activated graphite block includes: introducing argon at a pressure of 5-50 Pa, applying a power of 50-200 W for 5-15 minutes of ion etching to obtain a graphite block with a nanoscale microscopically rough surface; introducing a mixed gas of hydrogen and nitrogen with a volume ratio of 4:1 into the graphite block with the nanoscale microscopically rough surface, applying a power of 150-250 W for 5-8 minutes of surface activation treatment to obtain the activated graphite block.

[0009] Preferably, the activated graphite block is subjected to CVD deposition with trichloromethylsilane and methane gas in a preset ratio to obtain a CVD-deposited graphite block, including: placing the activated graphite block in a CVD reaction chamber, introducing trichloromethylsilane and methane gas in a ratio of 1:1.5, and depositing for 0.5 - 1 hour to obtain a first silicon carbide transition layer; adjusting the gas ratio of trichloromethylsilane to methane gas to 1:1, and depositing on the carbon-rich silicon carbide transition layer for 1 - 2 hours to obtain a second silicon carbide transition layer; adjusting the gas ratio of trichloromethylsilane to methane gas to 1.2:1, and depositing on the second silicon carbide transition layer for 1.5 - 2 hours to obtain the CVD-deposited graphite block.

[0010] Preferably, the CVD-deposited graphite block is subjected to CVD deposition with a boron trichloride concentration gradient doping to obtain a doped graphite block, including: introducing a boron trichloride gas with a concentration of 0.5 - 1% and mixing it with a reaction gas, and depositing on the CVD-deposited graphite block to obtain a first doped layer; introducing a boron trichloride gas with a concentration of 0.2 - 0.3% for deposition on the first doped layer to obtain a second doped layer; introducing a boron trichloride gas with a concentration of 0.05 - 0.1% for deposition on the second doped layer to obtain the doped graphite block.

[0011] Preferably, the step of introducing a boron trichloride gas with a concentration of 0.5 - 1% and mixing it with a reaction gas, and depositing on the CVD-deposited graphite block to obtain a first doped layer includes: evacuating the CVD furnace to 100 - 500 Pa to obtain a pretreated graphite block; introducing a mixed gas of boron trichloride, trichloromethylsilane and methane to the pretreated graphite block, controlling the concentration of boron trichloride to be 0.5 - 1%, and the total gas flow rate to be 200 - 300 mL / min, and depositing for 2 hours to obtain the first doped layer.

[0012] Preferably, the doped graphite block is subjected to structural gradient CVD deposition at a preset temperature and gas flow rate to obtain a silicon carbide coating, including: heating the doped graphite block to 1100 - 1150 °C, adjusting the reaction gas flow rate to 150 - 250 mL / min, and depositing for 2 - 3 hours to obtain a nanocrystalline structure layer; raising the temperature of the nanocrystalline structure layer to 1200 - 1300 °C, adjusting the gas flow rate to 250 - 350 mL / min, and depositing for 2 - 3 hours to obtain a microcrystalline structure layer; raising the temperature of the microcrystalline structure layer to 1350 - 1400 °C, adjusting the gas flow rate to 350 - 450 mL / min, and depositing for 2 - 3 hours to obtain the silicon carbide coating.

[0013] Preferably, heating the doped graphite block to 1100 - 1150 °C, adjusting the flow rate of the reaction gas to 150 - 250 mL / min, and depositing for 2 - 3 hours to obtain a nanocrystalline structure layer, including: heating the doped graphite block to 1100 - 1150 °C at a heating rate of 5 - 10 °C / min to obtain a substrate at a predetermined temperature; introducing a mixed gas of trichloromethylsilane and methane into the substrate at the predetermined temperature, controlling the flow rate to 150 - 250 mL / min, and depositing for 2 - 3 hours to obtain the nanocrystalline structure layer.

[0014] Preferably, after obtaining the silicon carbide coating, it further includes: placing the silicon carbide coating in a temperature environment of 1500 - 1600 °C and annealing for 2 - 4 hours to obtain an annealed silicon carbide coating.

[0015] The embodiment of the present application also provides a composite material, including a graphite block and a silicon carbide coating on the surface of the graphite block, and the silicon carbide coating is prepared by any of the methods for preparing a silicon carbide coating on the surface of a graphite block described above.

[0016] The present application has the following technical effects:

[0017] By using metal silicon particles to react with a graphite block in a vacuum environment to form an initial silicon carbide layer firmly bonded to the substrate, it provides a stable foundation for subsequent processing; and by using argon plasma etching and hydrogen / nitrogen mixed gas activation treatment, the activity and roughness of the surface of the initial silicon carbide layer are significantly improved, and the bonding strength with the subsequent CVD layer is enhanced, and the interfacial shear strength is increased by 40 - 60% compared with the traditional process. Description of the Drawings

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. The drawings herein are incorporated into the specification and constitute a part of this specification. These drawings show embodiments consistent with the present disclosure and are used together with the specification to illustrate the technical solutions of the present disclosure. It should be understood that the following drawings only show some embodiments of the present disclosure, and therefore should not be regarded as limiting the scope. For those of ordinary skill in the art, other related drawings can be obtained based on these drawings without creative efforts.

[0019] Figure 1 It is a schematic flow chart of the method for preparing a silicon carbide coating on the surface of a graphite block provided by the embodiment of the present application;

[0020] Figure 2 It is a schematic diagram of the formation of an initial silicon carbide layer by silicon vapor reaction in the embodiment of the present application;

[0021] Figure 3It is a schematic diagram of the interface activation pretreatment in the embodiments of the present application. Detailed implementation manners

[0022] To make the objectives, technical solutions and advantages of the embodiments of the present disclosure clearer, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present disclosure. Apparently, the described embodiments are only some of the embodiments of the present disclosure, rather than all of the embodiments. Components of the embodiments of the present disclosure described and illustrated herein generally may be arranged and designed in a variety of different configurations. Therefore, the detailed description of the embodiments of the present disclosure provided herein is not intended to limit the scope of the claimed present disclosure, but merely represents selected embodiments of the present disclosure. All other embodiments obtained by those skilled in the art based on the embodiments of the present disclosure without creative efforts fall within the scope of the present disclosure.

[0023] It should be noted that like reference numerals and letters denote like items in the following figures, and thus, once an item is defined in one figure, it will not be further defined and explained in subsequent figures.

[0024] As used herein, the term "and / or" merely describes an association relationship and indicates that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the term "at least one" as used herein means any one of a plurality or any combination of at least two of a plurality. For example, including at least one of A, B, and C may represent including any one or more elements selected from the set composed of A, B, and C.

[0025] As Figure 1 shown, an embodiment of the present application provides a method for preparing a silicon carbide coating on the surface of a graphite block, including:

[0026] Step 1: React metal silicon particles with the graphite block in a vacuum environment to obtain a graphite block with an initial silicon carbide layer;

[0027] Exemplarily, first, place high-purity metallic silicon particles with a particle size of 5 - 10 mm in a graphite crucible at the bottom of the reaction device, and place the graphite block to be processed on a bracket about 30 mm away from the silicon material in the crucible. Then place the entire device in a high-temperature furnace, and under a vacuum of 500 Pa, heat it at a rate of 10 °C / min to a temperature range of 1700 - 1800 °C and hold for 2 - 4 hours for reaction. During this process, the metallic silicon evaporates at high temperature to form silicon vapor, and the silicon vapor directly reacts with the carbon atoms on the surface of the graphite matrix to form an initially firmly chemically bonded silicon carbide layer. The thickness of this initial layer is usually 10 - 20 μm, and it is tightly bonded to the graphite matrix, providing a good foundation for subsequent processing. After the reaction is completed, naturally cool to room temperature and take out the sample to obtain a graphite block with an initially formed silicon carbide layer.

[0028] Step 2: Place the graphite block with the initially formed silicon carbide layer in a plasma processing chamber, perform surface etching via argon plasma, and perform surface activation treatment using a mixed gas of hydrogen and nitrogen to obtain an activated graphite block.

[0029] This step is one of the key innovations of this method, and it optimizes the interface characteristics through plasma dual modification treatment. Exemplarily, first transfer the graphite block with the initially formed silicon carbide layer to the plasma processing chamber and evacuate it to a low-pressure state. Introduce high-purity argon gas at a pressure of 5 - 50 Pa, apply a power of 50 - 200 W to generate a stable argon plasma, and perform ion etching treatment on the sample surface for 5 - 15 minutes. This etching process can form a nano-scale microscopic rough structure on the silicon carbide surface, significantly increasing the surface area and mechanical interlocking effect. Subsequently, while keeping the chamber pressure unchanged, switch to a mixed gas of hydrogen and nitrogen with a volume ratio of 4:1, adjust the power to the range of 150 - 250 W, and perform surface activation treatment for 5 - 8 minutes. The hydrogen-nitrogen plasma treatment can form a large number of active sites and dangling bonds on the etched rough surface, significantly improving the surface chemical activity. Finally, introduce high-purity helium gas for 3 - 5 minutes of purging and cleaning to remove possible residual substances, and obtain an activated graphite block with ideal interface characteristics.

[0030] Step 3: Use the activated graphite block and perform CVD deposition with trichloromethylsilane and methane gas in a preset ratio to obtain a graphite block after CVD deposition.

[0031] This step realizes the stoichiometric ratio gradient transition of carbon and silicon contents in silicon carbide, which is the first stage of the multi-dimensional gradient design. Exemplarily, the activated graphite block is transferred to the CVD reaction chamber. First, trichloromethylsilane and methane gas are introduced for deposition in a ratio of 1:1.5 for 0.5 - 1 hour to form a carbon-rich silicon carbide transition layer. This carbon-rich layer has better chemical compatibility with the initially activated silicon carbide layer. Subsequently, the reaction gas ratio is gradually adjusted to 1:1 and deposition continues for 1 - 2 hours to form a stoichiometric silicon carbide transition layer on the carbon-rich layer. Finally, the gas ratio is adjusted to 1.2:1 and deposition is carried out for 1.5 - 2 hours to form a slightly silicon-rich silicon carbide layer. The whole process usually lasts for 3 - 5 hours. Through the gradual transition of the composition, the interfacial stress caused by the chemical composition difference between different layers is effectively reduced, laying a good foundation for subsequent processing.

[0032] Step 4: Perform CVD deposition with a boron trichloride concentration gradient doping on the graphite block after CVD deposition to obtain a doped graphite block.

[0033] This step realizes the doping element gradient transition, constituting the second stage of the multi-dimensional gradient design. Exemplarily, first, the graphite block after CVD deposition is re-put into the CVD reaction chamber, and the vacuum is pumped to 100 - 500 Pa. Then, boron trichloride gas with a concentration of 0.5 - 1% and a mixed reaction gas of trichloromethylsilane and methane are introduced, and the total gas flow rate is controlled at 200 - 300 mL / min for deposition for about 2 hours to form a first doped layer with high boron doping. Boron doping can significantly improve the conductivity and thermal stability of the silicon carbide layer. Subsequently, the boron trichloride concentration is reduced to the range of 0.2 - 0.3% and deposition continues to form a second doped layer with medium concentration. Finally, the boron trichloride concentration is further reduced to 0.05 - 0.1% to complete the deposition of the outermost low-concentration doped layer. The whole doping process usually lasts for 5 - 8 hours. Through the gradient change of the doping concentration, the performance gradient transition of the coating system is further optimized, and the thermal stress concentration caused by the sudden change of material properties is reduced.

[0034] Step 5: Perform structure gradient CVD deposition on the doped graphite block according to the preset temperature and gas flow rate to obtain a silicon carbide coating.

[0035] This step realizes the microstructural gradient transition and is the third stage of the multi-dimensional gradient design. Exemplarily, first, the doped graphite bulk material is heated to 1100 - 1150 °C at a heating rate of 5 - 10 °C / min, and the flow rate of the mixed gas of trichloromethylsilane and methane is controlled within the range of 150 - 250 mL / min for low-temperature deposition for 2 - 3 hours to form a nanocrystalline structure layer. The nanocrystalline structure has high toughness and interfacial bonding ability. Subsequently, the temperature is gradually increased to 1200 - 1300 °C, and at the same time, the gas flow rate is increased to 250 - 350 mL / min, and deposition continues for 2 - 3 hours to form a microcrystalline structure transition layer. Finally, the temperature is further increased to 1350 - 1400 °C, the gas flow rate is increased to 350 - 450 mL / min, and deposition is carried out for 2 - 3 hours to form an outer layer of well-oriented polycrystalline structure. The polycrystalline structure has excellent high-temperature stability and oxidation resistance. The entire structural gradient process usually lasts for 5 - 10 hours. Through the gradual transition of grain size and orientation, a smooth transition of the mechanical properties and thermal properties of the coating from the inside to the outside is achieved, further reducing the thermal stress concentration and improving the stability and service life of the coating system under high-temperature cyclic conditions.

[0036] Through the above five consecutive process steps, this method successfully realizes the multi-dimensional gradient transition from the graphite substrate to the silicon carbide coating, forming a silicon carbide composite coating with excellent interfacial bonding strength and high-temperature stability. Compared with the traditional process, the coating prepared by this method shows significantly improved stability in the 1600 °C thermal cycle test, with the interfacial peeling rate reduced by more than 85% and the shear strength increased by 40 - 90%, providing reliable technical support for applications in high-temperature extreme environments.

[0037] In an embodiment of the present application, as Figure 2 shown, the use of metal silicon particles and graphite bulk material to carry out a silicon vapor reaction in a vacuum environment to obtain a graphite bulk material with an initial silicon carbide layer includes:

[0038] Place metal silicon particles with a particle size of 5 - 10 mm at the bottom of the reaction device, and place the graphite bulk material in the reaction device;

[0039] Heat the reaction device to 1700 - 1800 °C at a heating rate of 10 °C / min under a vacuum of 500 Pa and react for 2 - 4 hours to obtain the graphite bulk material with the initial silicon carbide layer.

[0040] In this embodiment, the silicon vapor generated by the metal silicon particles at high temperature reacts with the carbon atoms on the surface of the graphite substrate to form an initial silicon carbide layer. This layer has good bonding strength with the graphite substrate and lays the foundation for subsequent treatment. During specific operation, the graphite bulk material can be placed at a position about 30 mm away from the silicon particles to ensure uniform reaction.

[0041] In one embodiment of the present application, as Figure 3 shown, placing the graphite block with the initial silicon carbide layer in a plasma processing chamber, performing surface etching via argon plasma, and performing surface activation treatment using a mixed gas of hydrogen and nitrogen to obtain the activated graphite block includes: introducing argon at a pressure of 5 - 50 Pa, applying a power of 50 - 200 W for 5 - 15 minutes of ion etching to obtain a graphite block with a nanoscale micro-rough surface; introducing a mixed gas of hydrogen and nitrogen with a volume ratio of 4:1 to the graphite block with the nanoscale micro-rough surface, applying a power of 150 - 250 W for 5 - 8 minutes of surface activation treatment to obtain the activated graphite block.

[0042] In this embodiment, plasma processing is one of the key innovations of this method. Argon plasma etching forms a nanoscale rough structure on the silicon carbide surface through physical collision, increasing the mechanical interlocking effect; while hydrogen / nitrogen mixed gas plasma processing forms a large number of active sites and dangling bonds on the surface, significantly improving the chemisorption ability of the subsequent CVD deposition layer. After the etching treatment, high-purity helium can be introduced for 3 - 5 minutes of purging and cleaning to remove residual substances.

[0043] In one embodiment of the present application, using the activated graphite block to perform CVD deposition with trichloromethylsilane and methane gas in a preset ratio to obtain the CVD-deposited graphite block includes: placing the activated graphite block in a CVD reaction chamber, introducing trichloromethylsilane and methane gas in a ratio of 1:1.5, depositing for 0.5 - 1 hour to obtain a first silicon carbide transition layer; adjusting the gas ratio of trichloromethylsilane and methane gas to 1:1, depositing on the carbon-rich silicon carbide transition layer for 1 - 2 hours to obtain a second silicon carbide transition layer; adjusting the gas ratio of trichloromethylsilane and methane gas to 1.2:1, depositing on the second silicon carbide transition layer for 1.5 - 2 hours to obtain the CVD-deposited graphite block.

[0044] In this embodiment, by adjusting the ratio of trichloromethylsilane and methane gas, a stoichiometric ratio gradient transition is achieved, from a carbon-rich to a stoichiometric ratio and then to a slightly silicon-rich silicon carbide layer, forming a gradient structure in the first dimension. This gradient design effectively alleviates the thermal stress caused by compositional differences between different layers and improves the overall stability of the coating system.

[0045] In one embodiment of the present application, performing CVD deposition with a boron trichloride concentration gradient doping on the graphite block after CVD deposition to obtain a doped graphite block, includes: introducing boron trichloride gas with a concentration of 0.5 - 1% and mixing it with the reaction gas, and performing deposition on the graphite block after CVD deposition to obtain a first doped layer; introducing boron trichloride gas with a concentration of 0.2 - 0.3% for deposition on the first doped layer to obtain a second doped layer; introducing boron trichloride gas with a concentration of 0.05 - 0.1% for deposition on the second doped layer to obtain the doped graphite block.

[0046] Wherein, the concentration refers to the volume percentage concentration of boron trichloride (BCl3) in the entire reaction gas mixture. That is to say, the boron trichloride gas accounts for 0.5 - 1% of the volume ratio in the total gas flow rate. This is a relatively low but effective doping concentration range, which is sufficient to achieve boron doping modification of the silicon carbide coating while avoiding coating structure defects that may be caused by too high a concentration.

[0047] The reaction gas mainly includes:

[0048] Trichloromethylsilane (CH3SiCl3): as a silicon source;

[0049] Methane (CH4): as a carbon source;

[0050] Hydrogen (H2): as a carrier gas and reducing atmosphere;

[0051] In this step, boron trichloride is used as a doping gas and mixed with the above main reaction gases. Trichloromethylsilane and methane are still the main reaction gases for forming the silicon carbide matrix, and their ratio usually remains in the range close to 1:1 (may be slightly adjusted to adapt to the doping process). Hydrogen, as a carrier gas, helps the reaction gases to be evenly distributed and creates a reducing atmosphere favorable for deposition. The addition amount of boron trichloride in this mixed gas is controlled within the range of 0.5 - 1%, so that boron atoms can partially replace carbon or silicon atoms in the silicon carbide lattice during the CVD process, thereby achieving the doping effect.

[0052] The entire reaction gas system usually also supplements with inert gases (such as argon or helium) to adjust the total flow rate and the partial pressure of the reaction gases, which is adjusted according to specific process requirements. The total gas flow rate is generally controlled within the range of 200 - 300 mL / min to ensure a uniform and stable deposition process.

[0053] In this embodiment, the doping element gradient forms a gradient structure in the second dimension. Boron doping not only improves the electrical conductivity and thermal stability of the silicon carbide layer, but also further reduces the interlayer stress through the change of the concentration gradient, optimizing the overall performance of the coating.

[0054] In one embodiment of the present application, boron trichloride gas with an introduction concentration of 0.5 - 1% is mixed with the reaction gas, and the graphite block after CVD deposition is deposited to obtain a first doped layer, including: evacuating the CVD furnace to 100 - 500 Pa to obtain a pretreated graphite block; introducing a mixed gas of boron trichloride, trichloromethylsilane, and methane into the pretreated graphite block, controlling the concentration of boron trichloride to be 0.5 - 1%, and the total gas flow rate to be 200 - 300 mL / min, and depositing for 2 hours to obtain the first doped layer.

[0055] In this embodiment, before the doping treatment, it is necessary to evacuate the CVD furnace to an appropriate pressure range to ensure the stability of the deposition process and the consistency of the doping effect. The control of the total gas flow rate is crucial for forming a uniform doped layer.

[0056] In one embodiment of the present application, the doped graphite block is subjected to structural gradient CVD deposition according to a preset temperature and gas flow rate to obtain a silicon carbide coating, including: heating the doped graphite block to 1100 - 1150 °C, adjusting the reaction gas flow rate to 150 - 250 mL / min, and depositing for 2 - 3 hours to obtain a nanocrystalline structure layer; raising the temperature of the nanocrystalline structure layer to 1200 - 1300 °C, adjusting the gas flow rate to 250 - 350 mL / min, and depositing for 2 - 3 hours to obtain a microcrystalline structure layer; raising the temperature of the microcrystalline structure layer to 1350 - 1400 °C, adjusting the gas flow rate to 350 - 450 mL / min, and depositing for 2 - 3 hours to obtain the silicon carbide coating.

[0057] In this embodiment, by controlling the temperature and gas flow rate, a gradient change from nanocrystalline to microcrystalline to polycrystalline structure is achieved, forming a gradient structure in the third dimension. Silicon carbide layers with different grain sizes have different mechanical and thermal properties, and this microstructure gradient further improves the thermal stability and mechanical properties of the coating system.

[0058] In one embodiment of the present application, heating the doped graphite block to 1100 - 1150 °C, adjusting the reaction gas flow rate to 150 - 250 mL / min, and depositing for 2 - 3 hours to obtain a nanocrystalline structure layer, including: heating the doped graphite block to 1100 - 1150 °C at a heating rate of 5 - 10 °C / min to obtain a substrate at a predetermined temperature; introducing a mixed gas of trichloromethylsilane and methane into the substrate at the predetermined temperature, regulating the flow rate to 150 - 250 mL / min, and depositing for 2 - 3 hours to obtain the nanocrystalline structure layer.

[0059] In this embodiment, controlling the heating rate is crucial for avoiding thermal stress generated in the graphite substrate and the deposited coating due to rapid temperature changes. An appropriate heating rate can ensure the structural integrity of the coating system during heating.

[0060] In one embodiment of the present application, after obtaining the silicon carbide coating, it further includes: placing the silicon carbide coating in a temperature environment of 1500 - 1600 °C and performing annealing treatment for 2 - 4 hours to obtain an annealed silicon carbide coating.

[0061] In this embodiment, high-temperature annealing treatment can further improve the crystallinity and internal structural integrity of the silicon carbide coating, release the residual stress generated during the deposition process, and optimize the overall performance and thermal stability of the coating.

[0062] Example 1: Preparation of Silicon Carbide Coating for Graphite Components in Aero-engines

[0063] Raw Materials and Equipment: Graphite Substrate: High-purity graphite block with a density of 1.75 g / cm 3 , sized 50 mm × 50 mm × 10 mm; Solid Silicon Material: 4N purity (99.99%); Metallic Silicon Particles, particle size 5 - 10 mm; Plasma Processing Equipment: Radio-frequency plasma processing system with a maximum power of 500 W; CVD Equipment: Vertical hot-wall CVD furnace with a maximum temperature of 1800 °C;

[0064] Process Flow:

[0065] First Step: Silicon Vapor Reaction

[0066] Place 10 g of solid silicon particles at the bottom of the graphite crucible and place the graphite substrate on the graphite support 30 mm away from the silicon material inside the crucible;

[0067] In the graphitization furnace, heat up to 1750 °C at a rate of 10 °C / min;

[0068] Keep it at a vacuum of 500 Pa for 3 hours, naturally cool to room temperature, and take out the sample;

[0069] Second Step: Interface Activation Pretreatment Transfer the sample to the plasma processing chamber;

[0070] Evacuate to 1 Pa, introduce high-purity argon gas, and adjust the pressure to 25 Pa;

[0071] Start the radio-frequency power supply, set the power to 120 W, and perform ion etching for 10 minutes;

[0072] Keep the same pressure, switch the gas to a hydrogen / nitrogen mixed gas (volume ratio 4:1), adjust the power to 180 W, perform surface activation treatment for 7 minutes, and introduce high-purity helium gas for purging for 4 minutes;

[0073] Step 3: Deposition of the gradient transition layer

[0074] Stage 1 (chemical stoichiometry gradient, total time 4 hours);

[0075] Initial stage (1 hour): The ratio of trichloromethylsilane to methane gas is 1:1.5;

[0076] Intermediate stage (1.5 hours): The gas ratio is gradually adjusted to 1:1;

[0077] Final stage (1.5 hours): The gas ratio is adjusted to 1.2:1;

[0078] Stage 2 (doped element gradient, total time 6 hours) Initial sub-stage (2 hours): 0.8% boron trichloride is introduced. Intermediate sub-stage (2 hours): The concentration of boron trichloride linearly decreases to 0.3%. Final sub-stage (2 hours): The concentration of boron trichloride decreases to 0.08%.

[0079] Stage 3 (structural gradient, total time 8 hours) Initial temperature 1120°C, gas flow rate 200 mL / min (2 hours). Intermediate temperature is gradually increased to 1250°C, flow rate 300 mL / min (3 hours), and final temperature is increased to 1380°C, flow rate 400 mL / min (3 hours).

[0080] Test results: Total coating thickness: 65 ± 3 μm (initial reaction layer is about 15 μm, gradient CVD layer is about 50 μm). After 50 thermal cycles at 1600°C, the interfacial delamination area is less than 2%. Shear strength: 35.6 MPa, 92.4% higher than the traditional process. Oxidation test: Exposed in air at 1500°C for 100 hours, the weight gain rate is less than 0.5%.

[0081] Example 2: Preparation of a silicon carbide coating for a high-temperature graphite product used in nuclear energy

[0082] Raw materials and equipment:

[0083] Graphite substrate: Nuclear-grade graphite tube with a density of 1.85 g / cm 3 , outer diameter 80 mm, inner diameter 60 mm, length 120 mm; Plasma equipment: Microwave plasma processing system, frequency 2.45 GHz; CVD equipment: Horizontal hot-wall CVD furnace equipped with a rotating sample stage;

[0084] Process flow: Similar to Example 1, but the main differences are: In the first step of the silicon vapor reaction, the graphite tube rotates at a speed of 5 rpm during the reaction to ensure a uniform reaction interface. The activation pretreatment uses microwave plasma with a power controlled at 350 W. Aluminum nitride doping is added during the deposition of the gradient transition layer, gradually decreasing from 0.3% to 0.05%. The graphite tube rotates throughout the process to ensure coating uniformity.

[0085] Test results:

[0086] Coating thickness uniformity: The thickness deviation between the inner and outer surfaces is less than 5%.

[0087] Thermal neutron absorption cross section: Less than 5.2×10-24 cm 2 After 100 thermal cycle tests at 1600°C, the interface peeling area is less than 1%. Oxidation resistance: When exposed to an air environment at 1450°C for 200 hours, the weight gain rate is less than 0.3%.

[0088] Comparative example 1:

[0089] The traditional double-layer silicon carbide coating process: According to the traditional process, the graphite block is successively prepared with a double-layer silicon carbide coating through two steps of silicon vapor reaction and CVD deposition. After the first step of reaction at 1700°C and 500 Pa for 3 hours, it directly enters the second step, and conventional CVD deposition is carried out at 1300°C for 25 hours. After 10 thermal cycle tests at 1600°C on the obtained coating, obvious peeling appears at the interface, and the peeling area accounts for about 28% of the total area. In the shear strength test, the interface strength is 18.5 MPa.

[0090] Comparative example 2:

[0091] Only interface activation pretreatment is adopted. An interface activation pretreatment step is added between the two steps of the traditional process, including 10 minutes of argon ion etching (power 150 W, pressure 20 Pa) and 6 minutes of hydrogen-nitrogen mixed gas plasma activation (power 200 W). The CVD deposition process parameters in the second step are the same as those in Comparative example 1. After 20 thermal cycle tests at 1600°C on the obtained coating, the interface peeling area accounts for about 12% of the total area. In the shear strength test, the interface strength is increased to 27.3 MPa.

[0092] Comparative example 3:

[0093] Only gradient transition layer design is adopted. On the basis of the traditional process, the second-step CVD deposition is changed to a three-stage gradient transition layer design, but no interface activation pretreatment is carried out. The three-stage deposition includes stoichiometric ratio gradient (4 hours), doping element gradient (6 hours), and structural gradient (8 hours). After 30 thermal cycle tests at 1600°C on the obtained coating, the interface peeling area accounts for about 8% of the total area. In the shear strength test, the interface strength is 25.1 MPa.

[0094] It can be seen from the above examples and comparative examples that the progressive scheme combining interface activation pretreatment and gradient transition layer design can significantly improve the interface bonding strength and high-temperature stability of the double-layer silicon carbide coating, especially in application scenarios that need to withstand extreme working conditions for a long time. In all test indicators, the technical solution of the present application is superior to the three comparative examples, especially in terms of thermal cycle stability, with the most significant improvement.

[0095] In summary, the method for preparing a silicon carbide coating on the surface of a graphite block provided by the present application, through a progressive interface optimization system combining interface activation pretreatment and gradient transition layer design, fundamentally solves the technical problems of defects existing at the interface of traditional double-layer silicon carbide coatings, such as easy peeling or cracking. The silicon carbide coating prepared by this method exhibits excellent thermal stability and interface bonding strength under high-temperature cycling conditions, providing reliable technical support for high-end application fields.

[0096] The present application also provides a composite material, including a graphite block and a silicon carbide coating on the surface of the graphite block. The composite material is prepared by any of the above methods for preparing a silicon carbide coating on the surface of a graphite block. The composite material combines the thermal conductivity and electrical conductivity of graphite with the high-temperature stability and oxidation resistance of silicon carbide, and is particularly suitable for a variety of extreme environment application scenarios. In the field of semiconductor manufacturing, the composite material can be used to manufacture high-temperature furnace components, wafer carriers, and diffusion furnace parts; in the field of aerospace, it can be used to manufacture thermal protection system components, engine combustion chamber components, and high-temperature gas channels; in the field of nuclear energy, it can be used to manufacture high-temperature gas-cooled reactor fuel element sheaths, neutron reflection materials, and control rod guide structures. The composite material still maintains structural integrity and functional stability in a high-temperature environment above 1600°C, making it an irreplaceable functional material under extreme working conditions.

[0097] Finally, it should be noted that the above embodiments are only specific implementation manners of the present disclosure, used to illustrate the technical solutions of the present disclosure, rather than limiting them. The protection scope of the present disclosure is not limited thereto. Although the present disclosure has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: any person skilled in the art within the technical scope disclosed by the present disclosure can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some of the technical features; and these modifications, changes, or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present disclosure, and should all be covered within the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be subject to the protection scope of the claims.

Claims

1. A method for preparing a silicon carbide coating on the surface of a graphite block, characterized in that: include: Using metallic silicon particles and graphite blocks to react with silicon vapor in a vacuum environment to obtain a graphite block having an initial silicon carbide layer; Placing the graphite block material having the initial silicon carbide layer in a plasma treatment chamber, performing surface etching via argon plasma, and performing surface activation treatment using a mixed gas of hydrogen and nitrogen to obtain an activated graphite block material; Using the activated graphite block, performing CVD deposition using trichloromethylsilane and methane gas in a preset ratio to obtain a CVD-deposited graphite block; Performing CVD deposition of boron trichloride concentration gradient doping on the graphite block after CVD deposition to obtain a doped graphite block; The doped graphite block is subjected to structural gradient CVD deposition according to a preset temperature and gas flow rate to obtain a silicon carbide coating.

2. The method for preparing a silicon carbide coating on the surface of a graphite block according to claim 1, characterized in that: The method uses metal silicon particles and graphite blocks to react with silicon vapor in a vacuum environment to obtain a graphite block having an initial silicon carbide layer, comprising: Placing metallic silicon particles with a particle size of 5-10 mm at the bottom of a reaction device, and placing the graphite block in the reaction device; The reaction device is heated to 1700-1800° C. at a heating rate of 10° C. / min under a vacuum degree of 500 Pa, and reacted for 2-4 hours to obtain the graphite block having the initial silicon carbide layer.

3. The method according to claim 1, characterized in that The graphite block material having the initial silicon carbide layer is placed in a plasma treatment chamber, surface etching is performed via argon plasma, and surface activation treatment is performed using a mixed gas of hydrogen and nitrogen to obtain the activated graphite block material, comprising: Argon gas is introduced at a pressure of 5-50 Pa, and ion etching is performed for 5-15 minutes at a power of 50-200 W to obtain a graphite block having a nano-scale microscopic rough surface; A mixed gas of hydrogen and nitrogen in a volume ratio of 4:1 is introduced into the graphite block having a nano-scale microscopic rough surface, and a surface activation treatment is performed for 5-8 minutes by applying a power of 150-250 W to obtain the activated graphite block.

4. The method for preparing a silicon carbide coating on the surface of a graphite block according to claim 1, characterized in that: The method of using the activated graphite block to perform CVD deposition using trichloromethylsilane and methane gas in a preset ratio to obtain a graphite block after CVD deposition comprises: Placing the activated graphite block in a CVD reaction chamber, introducing trichloromethylsilane and methane gas in a ratio of 1:1.5, and depositing for 0.5-1 hour to obtain a first silicon carbide transition layer; adjusting the gas ratio of trichloromethylsilane to methane gas to 1:1, depositing the carbon-rich silicon carbide transition layer for 1-2 hours to obtain a second silicon carbide transition layer; The gas ratio of trichloromethylsilane to methane gas is adjusted to 1.2:1, and the second silicon carbide transition layer is deposited for 1.5-2 hours to obtain a graphite block after CVD deposition.

5. The method for preparing a silicon carbide coating on the surface of a graphite block according to claim 1, characterized in that: The step of performing CVD deposition of boron trichloride concentration gradient doping on the CVD deposited graphite block to obtain the doped graphite block comprises: Introducing boron trichloride gas with a concentration of 0.5-1% and mixing it with the reaction gas to deposit the graphite block after CVD deposition to obtain a first doping layer; Introducing boron trichloride gas with a concentration of 0.2-0.3% into the first doping layer for deposition to obtain a second doping layer; Boron trichloride gas with a concentration of 0.05-0.1% is introduced into the second doping layer for deposition to obtain the doped graphite block.

6. The method for preparing a silicon carbide coating on the surface of a graphite block according to claim 5, characterized in that: The introduction of boron trichloride gas with a concentration of 0.5-1% and mixing with the reaction gas to deposit the graphite block after CVD deposition to obtain the first doping layer includes: The CVD furnace is vacuumed to 100-500 Pa to obtain a pretreated graphite block; A mixed gas of boron trichloride, trichloromethylsilane and methane is introduced into the pretreated graphite block, the concentration of the boron trichloride is controlled to be 0.5-1%, and the total gas flow rate is 200-300 mL / min. After 2 hours of deposition, the first doping layer is obtained.

7. The method for preparing a silicon carbide coating on the surface of a graphite block according to claim 1, characterized in that: The step of subjecting the doped graphite block to structural gradient CVD deposition at a preset temperature and gas flow rate to obtain a silicon carbide coating comprises: The doped graphite block is heated to 1100-1150° C., the reaction gas flow rate is adjusted to 150-250 mL / min, and the deposition is performed for 2-3 hours to obtain a nanocrystalline structure layer; The temperature of the nanocrystalline structure layer is raised to 1200-1300° C., the gas flow rate is adjusted to 250-350 mL / min, and the deposition is performed for 2-3 hours to obtain a microcrystalline structure layer; The temperature of the microcrystalline structure layer is raised to 1350-1400° C., the gas flow rate is adjusted to 350-450 mL / min, and the silicon carbide coating is obtained after 2-3 hours of deposition.

8. The method for preparing a silicon carbide coating on the surface of a graphite block according to claim 7, characterized in that: The doped graphite block is heated to 1100-1150° C., the reaction gas flow rate is adjusted to 150-250 mL / min, and the nanocrystalline structure layer is obtained after 2-3 hours of deposition, including: The doped graphite block is heated to 1100-1150° C. at a heating rate of 5-10° C. / min to obtain a matrix at a predetermined temperature; A mixed gas of trichloromethylsilane and methane is introduced into the substrate at the predetermined temperature, and the flow rate is adjusted to 150-250 mL / min. After 2-3 hours of deposition, the nanocrystalline structure layer is obtained.

9. The method for preparing a silicon carbide coating on the surface of a graphite block according to claim 1, characterized in that: After obtaining the silicon carbide coating, the method further comprises: The silicon carbide coating is placed in a temperature environment of 1500-1600° C. and annealed for 2-4 hours to obtain an annealed silicon carbide coating.

10. A composite material, characterized in that: It comprises a graphite block and a silicon carbide coating on the surface of the graphite block, wherein the silicon carbide coating is prepared by the method for preparing the silicon carbide coating on the surface of the graphite block according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing silicon carbide coating on graphite surface

    CN102850087A

  • Method for preparing surface SiC-C coating of carbon material in graphite-heating-element furnace

    CN106915975A

  • Multilayer silicon carbide / silicon dioxide / diamond composite self-supporting film and preparation method thereof

    CN111747414A

  • Protection method for graphite part of vacuum furnace

    CN111945129A

  • Interface layer structure of SiCf / SiC composite material fuel cladding and preparation method

    CN113004051A